Anti-leukemic effect of CDK9 inhibition in T-cell prolymphocytic leukemia - Johansson, Patricia (Ther Adv Hematol, 2020)
T-cell prolymphocytic leukemia (T-PLL) is an aggressive malignancy characterized by chemotherapy resistance and a median survival of less than 2 years. Here, we investigated the pharmacological effects of the novel highly specific cyclin-dependent kinase 9 (CDK9) inhibitor LDC526 and its clinically used derivate atuveciclib employing primary T-PLL cells in an ex vivo drug sensitivity testing platform. Importantly, all T-PLL samples were sensitive to CDK9 inhibition at submicromolar concentrations, while conventional cytotoxic drugs were found to be largely ineffective. At the cellular level LDC526 inhibited the phosphorylation at serine 2 of the RNA polymerase II C-terminal domain resulting in decreased de novo RNA transcription. LDC526 induced apoptotic leukemic cell death through down-regulating MYC and MCL1 both at the mRNA and protein level. Microarray-based transcriptomic profiling revealed that genes down-modulated in response to CDK9 inhibition were enriched for MYC and JAK-STAT targets. By contrast, CDK9 inhibition increased the expression of the tumor suppressor FBXW7, which may contribute to decreased MYC and MCL1 protein levels. Finally, the combination of atuvecliclib and the BCL2 inhibitor venetoclax exhibited synergistic anti-leukemic activity, providing the rationale for a novel targeted-agent-based treatment of T-PLL.